2020
DOI: 10.1111/anae.15150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra‐operative intravenous lidocaine on opioid consumption after bariatric surgery: a prospective, randomised, blinded, placebo‐controlled study

Abstract: Summary Peri‐operative lidocaine infusion warrants investigation in bariatric surgery because obese patients present different physiological and pharmacological risks. This single‐centre, prospective, randomised double‐blind placebo‐controlled study enrolled obese patients scheduled for laparoscopic bariatric surgery using an enhanced recovery protocol. Patients received either lidocaine (bolus of 1.5 mg.kg−1, then a continuous infusion of 2 mg.kg−1.h−1 until the end of the surgery, then 1 mg.kg−1.h−1 for 1 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…In addition, all patients in group L were observed closely during the perioperative period, and none of them showed cardiovascular toxicity (eg, increasing intervals, widening QRS complex) or any symptoms of toxicity (eg, dizziness, drowsiness, oral metal odor, mouth paresthesia, blurred vision). Based on previous studies 48,49 and the clinical signs of patients in our trial, the plasma concentration of lidocaine achieved at this infusion rate was less than the toxic concentration, which is within the safe range of medication.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, all patients in group L were observed closely during the perioperative period, and none of them showed cardiovascular toxicity (eg, increasing intervals, widening QRS complex) or any symptoms of toxicity (eg, dizziness, drowsiness, oral metal odor, mouth paresthesia, blurred vision). Based on previous studies 48,49 and the clinical signs of patients in our trial, the plasma concentration of lidocaine achieved at this infusion rate was less than the toxic concentration, which is within the safe range of medication.…”
Section: Discussionsupporting
confidence: 64%
“…15,50 There are no lidocaine-related adverse reactions in patients undergoing bariatric surgery. 49 However, we will further explore the efficacy of intravenous lidocaine in non-obese patients. Third, we did not compare lidocaine with opioids in combination with propofol for procedural sedation and analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for obstetric and gynaecologic surgery is limited and outcomes are mixed [ 59 ]. Further, a randomised double-blind placebo-controlled study of perioperative lidocaine infusion for patients undergoing bariatric surgery found no difference clinically in terms of postoperative outcomes including pain, nausea and vomiting, length of stay and oxycodone consumption [ 60 ]. On a different note, for breast surgery, lidocaine’s short-term benefit is limited; however, it may prove to be more useful long term as it has been reported to reduce the incidence of chronic postsurgical pain at three and six months after mastectomy [ 61 ].…”
Section: Evidence On Postoperative Outcomementioning
confidence: 99%
“…Lidocaine infusions are controversial in that some studies have shown decreased postoperative pain scores and opioid consumption 64 and others have shown no difference. 65 While there may be evidence for the beneficial effects of individual agents, the ideal combination therapy has not yet been determined.…”
Section: Opioid-sparing Anesthesia and Analgesiamentioning
confidence: 99%